Modeling runoff components as a function of soil macropores in a forest watershed of Durango, Mexico - Návar, José; Lizárraga Mendiola, Liliana; Jiménez Gómez, Marco A. (REVISTA TERRA LATINOAMERICANA, 2017)
The prediction of streamflow production with mathematical techniques and the potential relationship to silvicultural practices in forest soils is important in conventional and sustainable forest management. In this paper, we report the effect of the presence and absence of soil macropores in streamflow production using a mass balance approach. Using daily measurements of precipitation (P) and pan evaporation (Et) from 1945 to 2007 and sub-models to estimate forest interception (I) and potential evapotranspiration (Etp), surface runoff (Qs), sub-surface runoff (Qp), and changes in soil moisture content (θ) were calculated for the watershed La Rosilla II of El Salto, P.N., Durango, México. The results showed that absence of soil macropores increases Qs by 139 mm but diminishes Qp to 0. Actual evapotranspiration, Eta, increases from 506 mm to 541 mm and the average value of θ decreases from 0.43 to 0.38. As a consequence, the absence of soil macropores leads to lack of deep inf iltration by eliminating water recharge and augmenting surface runoff during the rainy season, which increases water available for Eta. Therefore, forest management practices must work towards forest maintenance to meet the objectives of conventional forest management to provide goods as well as to regulate the water cycle of forest soils to comply with one of the services furnished by forest ecosystems.